Provider attitudes toward evidence-based practice in autism: a mini-review - DeLucia, Elizabeth A.; Harden, Samantha M.; Scarpa, Angela (Frontiers in Child and Adolescent Psychiatry, 2024)
There are many established evidence-based practices (EBPs) for autistic youth which facilitate wellbeing and skill development across a range of domains. However, individuals on the autism spectrum are consistently underserved in mental health settings, limiting their access to these EBPs. Positive provider attitudes toward EBPs may increase their uptake or use. The current mini-review seeks to synthesize the literature regarding attitudes toward EBPs among providers working with autistic youth across a variety of settings (i.e., school, early intervention, and general mental health). Fifteen quantitative studies were included. The majority of studies (n = 13, 87%) utilized the Evidence Based Practice Attitudes Scale (EBPAS) or a variation of this scale. Attitudes toward EBPs were primarily used as a correlate or covariate, although some studies reported descriptive statistics of provider attitudes. When available, the reported results suggest that attitudes toward EBPs are moderately positive at baseline, although they vary between provider types. Two studies (13%) examined change in attitudes toward EBPs and suggested that they may be responsive to intervention. However, findings were mixed as to whether attitudes toward EBPs are predictive of EBP use/uptake. Implications and future directions are discussed.